Loading web-font TeX/Math/Italic

vineri, 13 septembrie 2024

Ciąg ... podstępów // Un șir cu ... șmecherie

 From the link https://www.deltami.edu.pl/2024/09/klub-44/

          Statement of the problem

          "The sequence \;a_0,\;a_1,\;a_2,\;...\; is defined by the formulas

           a_0=3,\;a_{n+1}=a_n^2-2,\;n=0,\;1,\;2,...\;. Calculate the limit

\lim_{n \to \infty}\frac{1}{a_n}\prod_{i=0}^{n-1}a_i


            or demonstrate that this limit does not exist."

The demonstration is from the same cited place .

          ANSWER : The limit is  \frac{1}{\sqrt{5}}.

          Proof : Personal preamble CiP

             A first observation is that \;a_n>2. (It would be too pedantic to prove this by induction; however: a_0>2\; and assuming a_n>2\; we get

 a_{n+1}=a_n^2-2>2^2-2=2.)

          We have, because a_n>2,

\;\;a_{n+1}-a_n=a_n^2-2-a_n=(a_n+1)(a_n-2)>0, so a_{n+1}>a_n, meaning the sequence (a_n)_{n\geqslant 0} is strictly increasing.

         Then we have  a_n\geqslant n+3 (an extremely poor estimate). (Induction is equally trivial: a_0\geqslant 3, and assuming \;a_n \geqslant n+3, result

 a_{n+1}\geqslant (n+3)^2-2=n^2+6n+7\geqslant n+4.)

However, from the above it follows that

\lim_{n \to \infty}a_n=\infty \;. \tag{1}

I wrote all this to justify the statement "Jasne, że a_n \to \infty". Next, we copy the quoted solution.

<end Preamble>

          We will define the sequence (b_n)_{n \geqslant 0} by

 b_0=1,\;b_n=a_0\cdots a_{n-1},\;n=1,\;2,\dots 

 and we have to investigate the limit of the sequence \left ( \frac{b_n}{a_n}\right )_{n \geqslant 0}.

          We see that

b_{n+1}=a_n \cdot b_n \tag{2}

and we will prove by Induction that 

a_n^2-5\cdot b_n^2=4. \tag{3}

     Obvious \;a_0^2-5\cdot b_0^2=3^2-5\cdot 1=4, and assuming (3) true, result

a_{n+1}^2-5\cdot b_{n+1}^2 \overset{def}{\underset{(2)}{=}}(a_n^2-2)^2-5 \cdot (a_n\cdot b_n)^2=\underline{a_n^4}-4a_n^2+4-\underline{5a_n^2b_n^2}=\underline{a_n^2}\cdot (a_n^2-5b_n)-4a_n^2+4 \underset{(3)}{=}a_n^2\cdot 4-4a_n^2+4=4

so (3) also occurs for \;n+1. This complete the Induction.

     Now we have 

\left (\frac{b_n}{a_n} \right )^2=\frac{b_n^2}{a_n^2}\underset{(3)}{=}\frac{\frac{a_n^2-4}{5}}{a_n^2}=\frac{a_n^2-4}{5a_n^2}=\frac{1}{5}-\frac{4}{5}\cdot \frac{1}{a_n^2}\xrightarrow{(1)}\frac{1}{5}-\frac{4}{5}\cdot 0=\frac{1}{5}.

Therefore \;\frac{b_n}{a_n} \to \frac{1}{\sqrt{5}}.

\blacksquare


Niciun comentariu:

Trimiteți un comentariu